Discovery and quantification of plastic particle pollution in human blood. (May 2022) - Leslie, Heather A.; van Velzen, Martin J.M.; Brandsma, Sicco H.; Vethaak, A. Dick; Garcia-Vallejo, Juan J.; Lamoree, Marja H.
Graphical abstract: Fig. S1. Schematic to accompany the paper (optional graphical abstract). Highlights: A method was validated for polymer mass concentrations in human whole blood. Polymers from plastics were detected and quantified in human blood. Polymers in human blood represent several high production volume plastics. Blood donors were from general public. Quality control of background plastic throughout sampling and analysis is key. Abstract: Plastic particles are ubiquitous pollutants in the living environment and food chain but no study to date has reported on the internal exposure of plastic particles in human blood. This study's goal was to develop a robust and sensitive sampling and analytical method with double shot pyrolysis - gas chromatography/mass spectrometry and apply it to measure plastic particles ≥700 nm in human whole blood from 22 healthy volunteers. Four high production volume polymers applied in plastic were identified and quantified for the first time in blood. Polyethylene terephthalate, polyethylene and polymers of styrene (a sum parameter of polystyrene, expanded polystyrene, acetonitrile butadiene styrene etc.) were the most widely encountered, followed by poly(methyl methacrylate). Polypropylene was analysed but values were under the limits of quantification. In this study of a small set of donors, the mean of the sum quantifiable concentration of plastic particles in blood was 1.6 µg/ml, showing a first measurement of the mass concentration of the polymeric component of plastic in human blood. This pioneering human biomonitoring study demonstrated that plastic particles are bioavailable for uptake into the human bloodstream. An understanding of the exposure of these substances in humans and the associated hazard of such exposure is needed to determine whether or not plastic particle exposure is a public health risk.